2021
DOI: 10.3389/fmed.2020.563893
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Expression in Kidney and Testis May Cause Kidney and Testis Infection in COVID-19 Patients

Abstract: In December 2019, a new type of pneumonia caused by SARS-Cov-2 (COVID-19) occurred in Wuhan and has been discovered in many countries around the world. ACE2 (angiotensin-converting enzyme 2) has been shown to be one of the major receptors that mediate the entry of SARS-Cov-2 into human cells. Here in this study, we used the online datasets to analyze ACE2 expression in different human organs. The results indicated that ACE2 highly expresses in renal tubular cells, Sertoli cells, Leydig cells, and cells in semi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(133 citation statements)
references
References 36 publications
3
127
0
3
Order By: Relevance
“…They are composed of sperm-producing cells (spermatogonia) and the supporting Sertoli cells. ACE2 is highly expressed in testicular cells, mainly distributed in spermatogonia, Leydig, and Sertoli cells ( 4 , 5 , 67 ), which indicates that the testis could be a potential target for SARS-CoV-2. If the virus causes damage to these cells, the spermatogenesis process will be affected.…”
Section: Discussionmentioning
confidence: 99%
“…They are composed of sperm-producing cells (spermatogonia) and the supporting Sertoli cells. ACE2 is highly expressed in testicular cells, mainly distributed in spermatogonia, Leydig, and Sertoli cells ( 4 , 5 , 67 ), which indicates that the testis could be a potential target for SARS-CoV-2. If the virus causes damage to these cells, the spermatogenesis process will be affected.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is another organ with elevated ACE-2 expression. The renal tubular cells are known to express high levels of ACE-2 [69]; however, no research evidence has been reported for the SARS-CoV-2 invoked kidney injury. In a statistical survey of 1099 COVID-19 patients, 0.5% reported acute kidney injury with a severity rate of 83.3%.…”
Section: Angiotensin-converting Enzyme 2 (Ace-2)mentioning
confidence: 99%
“…In a statistical survey of 1099 COVID-19 patients, 0.5% reported acute kidney injury with a severity rate of 83.3%. In some COVID-19 patients, SARS-CoV-2 was detected in the urine [69]. Additional studies are immediately warranted to test whether SARS-CoV-2 infections cause kidney damage, if so, the mechanisms involved in such cellular damage.…”
Section: Angiotensin-converting Enzyme 2 (Ace-2)mentioning
confidence: 99%
“…There are two ACE isoenzymes in the testis, namely the somatic (sACE) and testicular (tACE) isoforms, whereas the testicular and somatic isoforms of ACE2 are identical. Among all the tissues in the body, the testes have nearly the highest levels of ACE2 mRNA and protein expression (Fan et al 2021). Interestingly, the testicular expression of ACE2 is age related and is highest in men in their 30s and lowest in men in their 60s.…”
Section: Testicular Ace2mentioning
confidence: 99%